Kinetics of fatigue crack growth and crack paths in the old puddled steel after 100-years operating time - G. Lesiuk; M. Szata (Fracture and Structural Integrity)
The goal of the authors’ investigations was determination of the fatigue crack growth in fragments of steel structures (of the puddled steel) and its cyclic behavior. Tested steel elements coming from the turn of the 19th and 20th were gained from still operating ancient steel construction (a main hall of Railway Station, bridges etc.). This work is a part of investigations devoted to the phenomenon of microstructural degradation and its potential influence on their strength properties. The analysis of the obtained results indicated that those long operating steels subject to microstructure degradation processes consisting mainly in precipitation of carbides and nitrides inside ferrite grains, precipitation of carbides at ferrite grain boundaries and degeneration of pearlite areas [1, 2]. It is worth noticing that resistance of the puddled steel to fatigue crack propagation in the normalized state was higher. The authors proposed the new kinetic equation of fatigue crack growth rate in such a steel. Thus the relationship between the kinetics of degradation processes and the fatigue crack growth rate also have been shown. It is also confirmed by the materials research of the viaduct from 1885, which has not shown any significant changes in microstructure. The non-classical kinetic fatigue fracture diagrams (KFFD) based on deformation () or energy (W) approach was also considered. In conjunction with the results of low- and high-cycle fatigue and gradual loss of ductility as a consequence (due to the microstructural degradation processes) - it seems to be a promising construction of the new kinetics fatigue fracture diagrams with the energy approach.